Pengaruh Konten dan Promosi Food Vlogger @Kokobuncit terhadap Minat Kuliner di Kalangan Mahasiswa Tata Boga Unesa - Chairunnisa A.H.P, Vanya; Handajani, Sri; Kharnolis, Mein; Romadhoni, Ita Fatkhur (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to determine (1) the influence of food vlogger @kokobuncit's content on culinary interest among UNESA culinary students, (2) the influence of food vlogger @kokobuncit's promotion on culinary interest among UNESA culinary students, (3) the influence of content and promotion food vlogger on culinary interest among UNESA culinary students. This research uses a survey method with a questionnaire data collection instrument via Google Forms. The subjects of this research are active students of the UNESA Culinary Education Bachelor's study program who meet the criteria, namely domiciled in Surabaya, aged 19-23 years, understand culinary, follow the @kokobuncit account or have watched food vlogger content @kokobuncit, and follow culinary trends in Surabaya via the @kokobuncit account. The number of respondents to this research was 50 people. The data was processed using multiple regression analysis for partial tests and simultaneous tests. The research results showed that: (1) the content of food vlogger @kokobuncit had an effect on culinary interest with a value of 4.430; (2) promotion of food vlogger @kokobuncit influences culinary interest with a value of 2.608; (3) content and promotion of food vlogger @kokobuncit simultaneously influence culinary interest with a value of 42.146 and an R square value of 0.642 or an influence size of 64.2%. Keywords: content, food vlogger, promotion, Instagram, culinary interest